2023
DOI: 10.2188/jea.je20220244
|View full text |Cite
|
Sign up to set email alerts
|

Reporting Race and Ethnicity in Population Health and Clinical Research From Japan

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process which may lead to differences between this version and the Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…The prevalence of osteoporosis differs from country to country [8], and our manuscript would add to the previous evidence of the Japanese population with another European population. Furthermore, recent evidence has demonstrated that there are health disparities among a variety of diseases [26][27][28], and this study would also concur with such research. Secondly, we were able to validate the methods with two independent examiners, while the analysis by Ishikawa et al [12] was conducted by only one personnel member.…”
Section: Discussionsupporting
confidence: 89%
“…The prevalence of osteoporosis differs from country to country [8], and our manuscript would add to the previous evidence of the Japanese population with another European population. Furthermore, recent evidence has demonstrated that there are health disparities among a variety of diseases [26][27][28], and this study would also concur with such research. Secondly, we were able to validate the methods with two independent examiners, while the analysis by Ishikawa et al [12] was conducted by only one personnel member.…”
Section: Discussionsupporting
confidence: 89%
“…Although the current residence of the participants is Japan, we have not been able to obtain information on the past residential history of the patients. Furthermore, although this may be di cult due to various reasons [31,32], comparative studies between other race and ethnicity residing in Japan, or Japanese living in other countries would be necessary. Such data would be of great use in the clinical setting, as this may identify the differences in the clinical features between the local, national patients, compared to the local, non-national patients and patients that are visiting from abroad for a short term [33].…”
Section: Discussionmentioning
confidence: 99%
“…Although the current residence of the participants is Japan, we have not been able to obtain information on the past residential history of the patients. Furthermore, although this may be challenging due to various reasons, [32,33], comparative studies between other races and ethnicities residing in Japan, or Japanese living in other countries would be necessary. Such data would be of immense value in the clinical setting, as this may identify the differences in the clinical features between the local, national patients, compared to the local, non-national patients and patients that are visiting from abroad for a short term [34].…”
Section: Discussionmentioning
confidence: 99%